Government spending volatility and the size of nations - Davide Furceri; Marcos Poplawski Ribeiro (European Central Bank (ECB), 2008)
This paper provides empirical evidence showing that smaller countries tend to have more volatile government spending for a sample of 160 countries from 1960 to 2000. We argue that the larger size of a country decreases the volatility of government spending because it acts as an insurance against idiosyncratic shocks, and it leads to increasing returns to scale due to the higher ability of the government to spread its cost of financing over a larger pool of taxpayers. The results are robust to different time and country samples, different econometric techniques and to several sets of control variables. The analysis also evinces that country size is negatively related to the discretionary part of government spending and to the volatilities of most of the government spending items.
Keywords: E62; H10; 330; Country Size; Fiscal Policy; fiscal volatility; government size; H10; JEL: E62; Öffentliche Ausgaben; Volatilität; Finanzpolitik; Landesgröße; Vergleich; Welt